Infiltrative Basal Cell Carcinoma of the Head: Factors Influencing Bone Invasion and Surgical Outcomes - Anđela Dimkić Milenković; Vladimir Milenković; Masa Petrovic; Ana Tomic; Aleksandar Matejic; Nina Brkic; Milan Jovanović (Life)
Basal cell carcinoma (BCC) is the most prevalent form of skin cancer, with infiltrative subtypes presenting significant clinical challenges due to their aggressive behavior and potential for deep tissue and bone invasion. This study aimed to evaluate factors associated with bone infiltration and surgical bone removal in patients with infiltrative BCC. A prospective cohort of 100 patients with histologically confirmed infiltrative BCC was analyzed retrospectively. Clinical, histopathological, and imaging data were assessed to identify predictors of tumor behavior. Tumor size, histological subtype, and disease duration emerged as significant factors associated with bone invasion and resection. Logistic regression analysis identified tumor length as the most significant predictor of both bone infiltration (OR = 1.102, p < 0.001) and surgical bone removal (OR = 1.105, p < 0.001). Aggressive subtypes, such as infiltrative and morpheaform BCC, were more likely to invade bone and exhibited higher recurrence rates. While these findings highlight the importance of early detection and individualized treatment strategies, the absence of data on sun exposure and urban-rural residency limits the broader applicability of the results. Future research addressing these variables will provide a more comprehensive understanding of BCC aggressiveness and improve clinical management of this malignancy.